Analisis Dampak Pandemi Covid-19 terhadap Neraca Perdagangan di Kawasan Asia Tahun 2020 - Heva Nofi Wahyuningsih (Universitas Diponegoro, 2022)
This study aims to determine the extent of the impact of Pandemic Covid-19 on the trade balances of countries in the Asian Region. Furthermore, the independent variables used in the study include real exchange rates, gross domestic product, pandemic covid-19 and interaction of pandemic covid-19 with gross domestic product. Pandemic Covid-19 variable uses the number of positive confirmed cases of this virus. The dependent variable in the study is the trade balance. The data used are secondary data obtained from the World Bank, Financial Data & Economic Indicators (CEIC) and Trading Economics, covering 30 countries in the Asian Region for the period I-IV year 2020. This study uses the balanced panel data method with the fixed effect model (FEM). The research used the estimation technique of fixed effect model (FEM), which was selected based on the result of the Chow and Hausman test. The results show that Pandemic Covid-19 affects the aggregate supply side, namely production activities in a country due to mobility restrictions, so that the level of output produced will experience a decline. When the level of output in a country decreases, it will have an impact on the level of demand for goods and services demanded by people abroad. Pandemic Covid-19, real exchange rate and gross domestic product variable had a negative effect on the trade balance. If there is an increase of pandemic covid-19 cases, it will later affect on the decrease of ecport activities. Likewise, if there is an increase on gross domestic product and real exchange rate, it will later affect on the increase of import activities. This negative affect will result a deficit in trade balance.